Satisfaction by Design: Nurses Creating Hospital Spaces That Work - Joe Don Cavender (JONA: The Journal of Nursing Administration, 2026)
Objective: To evaluate the impact of frontline nurse involvement in hospital design through a structured program evaluation using the Context, Input, Process, and Product (CIPP) Model. Background: Nurses are primary users of hospital environments yet are often underrepresented in planning and design despite their expertise in workflow, safety, and patient‑family needs. Methods: This mixed-methods program evaluation examined a nurse advisor model implemented during the planning of a 552-bed pediatric hospital. Data were collected from 21 participants (14 design team members and 7 nurse advisors) using Likert-scale surveys and semi-structured focus groups aligned with CIPP domains. Results: Advisor satisfaction with nurse involvement was significantly higher than observed in prior design projects ( Z = −1.983, P = 0.047, r = −0.75), whereas design team satisfaction remained stable. Preparation and training received the lowest satisfaction ratings ( M = 2.76, SD = 1.14), while nurse-influenced design elements ( M = 4.10, SD = 1.07) and final design outcomes ( M = 3.90, SD = 1.17) received the highest ratings. Higher design team satisfaction with nurse preparation was associated with both more effective collaboration (ρ = 0.621, P = 0.018) and satisfaction with nurse-influenced design elements (ρ = 0.566, P = 0.044). Qualitative findings highlighted nurses’ roles as translators of frontline experience into design decisions and described perceived impacts on emergency department patient flow, staff respite and lactation spaces, decedent-care environments, and other human-centered features. Conclusions: Structured nurse participation in hospital planning was perceived as strengthening collaboration, credibility, and influence over design decisions. This nurse advisor model offers a transferable approach to more clinically informed, human-centered design processes.